Temporal symmetric pulses and symmetry breaking in generalized saturable Kerr-like media - Jasiński, Jerzy (Photonics Letters of Poland, 2009)
In the paper the propagation of temporal pulses through generalized saturable nonlinear Kerr-like media is described analytically. The influence of symmetry conditions on relations between phase and amplitude is analyzed. These relations introduced into a canonical description of propagation enable a solution of the Euler-Lagrange equations. The accuracy of a canonical description is discussed. Full Text: PDF References: K. Hizanidis, D. J. Frantzeskakis, C. Polymilis,"Exact travelling wave solutions for a generalized nonlinear Schrödinger equation", J. Phys. A, 29, 7687, (1996)[CrossRef] F.G. Bass, V.V. Konotop, S.A. Puzenko,"Dark solitary waves in a generalized version of the nonlinear Schrödinger equation", Phys. Rev. A 46, 4185, (1992)[CrossRef] J. Jasiński,"Bright solitons of generalized nonlinear Schrödinger equation", Opt. Comm. 172, 325, (1999)[CrossRef] D. Anderson,"Variational approach to nonlinear pulse propagation in optical fibers", Phys. Rev. A, 27, 3135, (1983)[CrossRef] C. Sulem, P.L. Sulem, The Nonlinear Schrödinger Equation: SelfFocusing and Wave Collapse, (New York, Springer-Verlag, 1999) G.P. Agrawal, Lightwave technology:telecommunications systems, pp. 137-142, Wiley Interscience, Hoboken, 2005 H. Goldstein, C. Poole, J. Safko, Classical Mechanics, (Addison Wesley, San Francisco, 2000)